PENGEMBANGAN WISATA LUMBA-LUMBA BERBASIS EKOLOGI DI PANTAI LOVINA BULELENG BALI - A.A.A Ribeka M.Purwahita (Jurnal AKSES, 2019)
The development of Maritime Tourism in Indonesia is very high so that it can increase the country's foreign exchange earnings. The visit of tourists who come to Lovina beach is mostly to enjoy nature with a quite beautiful beach panorama. One of the main attractions possessed by Lovina Beach is watching dolphin attractions directly in the middle of the beach, where this activity can only be seen on Lovina Beach, located in the North Bali region.Tourists who come for a vacation to Lovina beach and enjoy dolphin tourism activities in general have a direct awareness of participating in preserving and maintaining the cleanliness of the beaches in Lovina Beach. This will have an impact on the continuity of dolphin tourism activities so that it continues to run and provides many benefits for various parties. The development of ecology-based dolphin tourism on Lovina Beach is with the aim of maintaining the survival of dolphins and the preservation of marine and coastal areas on the coast of Lovina so this not only involves the government but also from various parties. These activities require the involvement of the wider community, especially communities around the Lovina beach to provide and increase awareness and understanding of the importance of preserving the sea and the preservation of the coast, given that marine tourism activities are not only for the present but can continue to be utilized in the future.